Three-dimensional structure NiCoP / CoMoO4 composite material nanorod as well as preparation method and application thereof

By preparing three-dimensional structure NiCoP/CoMoO4 composite nanorods, the problem of high cost of existing precious metal catalysts is solved, and the efficient and low-cost electrocatalytic hydrogen evolution performance is achieved, which is suitable for industrial applications.

CN119571373AActive Publication Date: 2025-03-07ANHUI NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411672583.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing catalysts for electrolyzing hydrogen production mainly rely on precious metals, such as Pt, Ir, and Ru, which leads to high costs and difficulty in large-scale promotion.

Method used

The three-dimensional structure NiCoP/CoMoO4 composite nanorods are used as high-efficiency hydrogen evolution electrocatalysts, and prepared by hydrothermal reaction, alkaline liquid heating reaction, nickel source solution soaking and phosphating to form a three-dimensional rod-like structure supported on nickel foam.

Benefits of technology

It achieves efficient electrocatalytic performance, has a large specific surface area and conductivity, and can continuously produce hydrogen at a current density of 50mA/cm-2 for 100h, which is low-cost and suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571373A_ABST
    Figure CN119571373A_ABST
Patent Text Reader

Abstract

The invention provides a three-dimensional structure NiCoP / CoMoO4 composite material nanorod and a preparation method and application thereof.The preparation method includes the steps that a cobalt source and a molybdenum source are mixed in water, foamed nickel is added, hydrothermal reaction is conducted, and cobalt molybdate is obtained; carrying out alkali etching and ion exchange to obtain NiCo (OH) 2 / CoMoO4; and then phosphating is carried out, and NiCoP / CoMoO4 is prepared. Compared with the prior art, the nanorod of the NiCoP / CoMoO4 composite material with the three-dimensional structure has the performance of large specific surface area and good conductivity, and can be used as a hydrogen evolution electrocatalyst with excellent performance. And meanwhile, the conductivity of cobalt molybdate is improved through the composite structure of cobalt nickel phosphide and cobalt molybdate, so that higher catalytic efficiency is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano material technology and electrocatalysis, and specifically relates to three-dimensional structured NiCoP / CoMoO4 composite material nanorods and a preparation method and application thereof. Background Art

[0002] The growing global energy demand has led to a worsening energy crisis, and the energy structure composed of fossil fuels as the main energy source can no longer meet the energy needs of today's society. At the same time, climate warming and environmental pollution caused by the severe consumption of fossil fuels have also become key issues that need to be urgently addressed in social development. Therefore, the search for clean energy has become a necessary condition for the development of sustainable and renewable energy systems in the future.

[0003] As an optimal energy carrier, hydrogen has the characteristics of high calorific value and pollution-free combustion products. It can be used as a clean energy to solve energy problems and reduce carbon emissions. Among them, "green hydrogen" produced by renewable energy is the most suitable hydrogen energy for clean energy conversion. At present, the most ideal "green hydrogen energy" preparation strategy is to produce hydrogen by electrolysis of water based on electrocatalytic reaction. In the process of preparing hydrogen by electrolysis of water, there are two half reactions, namely hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The working efficiency of the catalyst is the key to converting electrical energy into hydrogen energy.

[0004] At present, commercial water electrolysis materials are still mainly precious metals such as Pt, Ir, Ru and their compounds. However, precious metals have small reserves on the earth and high costs, which is not conducive to large-scale promotion and utilization.

[0005] Therefore, in the face of the industrial demand for low cost and high efficiency, it is urgent to develop non-precious metal-based catalysts with excellent electrohydrolysis performance. Summary of the invention

[0006] The purpose of the present invention is to provide a three-dimensional structure NiCoP / CoMoO4 composite material nanorod and a preparation method thereof; through the preparation method of the present invention, a three-dimensional structure NiCoP / CoMoO4 composite material nanorod morphology structure is obtained, so that it has a large specific surface area for catalytic reaction and high catalytic efficiency. And the price is low, and it has broad industrial application prospects.

[0007] Another object of the present invention is to provide an application of three-dimensional structured NiCoP / CoMoO4 composite nanorods as an efficient hydrogen evolution electrocatalyst. Compared with the original cobalt molybdate material, its hydrogen evolution performance and conductivity are greatly improved, thereby achieving efficient electrocatalytic performance.

[0008] The specific technical solutions of the present invention are as follows:

[0009] The method for preparing three-dimensional structured NiCoP / CoMoO4 composite nanorods comprises the following steps:

[0010] 1) mixing a cobalt source and a molybdenum source in water, adding nickel foam, and performing a hydrothermal reaction to obtain cobalt molybdate;

[0011] 2) placing the product of step 1) in an alkaline solution and heating the solution to react, thereby obtaining Co(OH)2 / CoMoO4;

[0012] 3) placing the product of step 2) in a nickel source solution, allowing it to stand and soak, to obtain NiCo(OH)2 / CoMoO4;

[0013] 4) Phosphating the product of step 3) to obtain NiCoP / CoMoO4.

[0014] In step 1), the nickel foam is pretreated before use to remove oxides and oil stains on the surface; the specific method is: the nickel foam is ultrasonically cleaned with 3M hydrochloric acid, anhydrous ethanol and deionized water in sequence.

[0015] In step 1), the molar ratio of the cobalt source to the molybdenum source is 2-2.5:1;

[0016] In step 1), the ratio of the cobalt source to water is 0.03-0.04 mol / L; the water is preferably deionized water;

[0017] In step 1), the cobalt source is selected from a soluble cobalt salt, preferably cobalt nitrate hexahydrate;

[0018] In step 1), the molybdenum source is selected from a soluble molybdenum salt, preferably ammonium molybdate tetrahydrate;

[0019] In step 1), the cobalt source and the molybdenum source are mixed in water, subjected to ultrasonic treatment and then stirred; the ultrasonic treatment time is 10 minutes and the stirring time is 5 minutes;

[0020] In step 1), the hydrothermal reaction has a reaction temperature of 150° C. and a reaction time of 6 h.

[0021] In step 2), the alkali solution is a potassium hydroxide solution with a concentration of 1 mol / L;

[0022] The volume of the alkali solution in step 2) is the same as the volume of the water in step 1);

[0023] In step 2), the heating reaction has a reaction temperature of 120° C. and a reaction time of 5 h.

[0024] In step 2), potassium hydroxide is used to etch the surface of the cobalt hydroxide to obtain Co(OH)2 / CoMoO4;

[0025] In step 3), the concentration of the nickel source solution is 0.1 mol / L, and the molar amount of nickel ions in the nickel source solution is 6-7 times the molar amount of the cobalt source in step 1);

[0026] In step 3), the nickel source is selected from a soluble nickel salt, preferably nickel nitrate;

[0027] In step 3), ion exchange is performed using a nickel source to obtain cobalt nickel hydroxide NiCo(OH)2 / CoMoO4;

[0028] In step 3), the soaking time is 1 hour;

[0029] In step 4), sodium hypophosphite is used for phosphating; the molar amount of the sodium hypophosphite is 4-12 times the molar amount of the cobalt source in step 1);

[0030] In step 4), the reaction atmosphere of the phosphating is high-purity nitrogen, the phosphating annealing temperature is 350-450° C., the phosphating annealing time is 2 hours, the phosphating is carried out in a tubular furnace, and the phosphating is carried out by vapor deposition method.

[0031] The three-dimensional NiCoP / CoMoO4 composite material nanorods provided by the present invention are prepared by the above method. The NiCoP / CoMoO4 material is a three-dimensional rod-shaped structure loaded on nickel foam, and mesopores are distributed on the three-dimensional rod-shaped structure, and the mesopore size is 2-5nm.

[0032] The application of the three-dimensional structure NiCoP / CoMoO4 composite material nanorods provided by the present invention as a hydrogen evolution electrocatalyst, the product prepared by the present invention has a large specific surface area, good conductivity and durability, and can be used as an excellent hydrogen evolution electrocatalyst. -2 At a current density of 50 mA / cm, the overpotential of the in-situ grown NiCoP / CoMoO4 nanorod material on nickel foam is only 147 mV. -2 The hydrogen evolution was continued for 100 h at a current density of 1.5 %.

[0033] Compared with the prior art, the preparation method of in-situ growth of NiCoP / CoMoO4 nanorod material on nickel foam disclosed in the present invention is a preparation reaction method with simple operation, low cost, mild conditions and green environmental protection. First, cobalt molybdate nanorods are generated on the conductive nickel foam, and then cobalt nickel phosphide with a mesoporous structure is constructed on the surface of cobalt molybdate. The constructed NiCoP / CoMoO4 material has a larger specific surface area than cobalt molybdate. At the same time, the composite structure of cobalt nickel phosphide and cobalt molybdate improves the conductivity of cobalt molybdate itself, thereby achieving higher catalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1This is a scanning electron microscope (SEM) image of the in-situ grown NiCoP / CoMoO4 composite nanorod material on nickel foam prepared in Example 1;

[0035] Figure 2 This is a transmission electron microscope (TEM) image of the in-situ grown NiCoP / CoMoO4 composite nanorod material on nickel foam prepared in Example 1;

[0036] Figure 3 The BET adsorption-desorption curve and pore size distribution diagram of the NiCoP / CoMoO4 composite nanorod material in situ grown on nickel foam prepared in Example 1;

[0037] Figure 4 The X-ray diffraction spectrum (XRD) of the NiCoP / CoMoO4 composite nanorod material in situ grown on nickel foam prepared in Example 1;

[0038] Figure 5 This is a high-resolution transmission electron microscopy (HRTEM) image of the in-situ grown NiCoP / CoMoO4 composite nanorod material on nickel foam prepared in Example 1;

[0039] Figure 6 Element mapping of the in-situ grown NiCoP / CoMoO4 composite nanorod material prepared in Example 1;

[0040] Figure 7 The linear scan cyclic voltammogram (LSV) of the NiCoP / CoMoO4 composite nanorod material in situ grown on nickel foam prepared in Example 1;

[0041] Figure 8 The cyclic voltammogram (CV) of the electrochemical double layer capacitance of the NiCoP / CoMoO4 composite nanorod material grown in situ on nickel foam prepared in Example 1;

[0042] Fig. 9 The electrochemically active surface area (ECSA) diagram of the NiCoP / CoMoO4 composite nanorod material in situ grown on nickel foam prepared in Example 1;

[0043] Fig.10 The electrochemical impedance spectroscopy (EIS) diagram of the in-situ grown NiCoP / CoMoO4 composite nanorod material on nickel foam prepared in Example 1;

[0044] Fig.11 The chronopotentiometry diagram of the in-situ grown NiCoP / CoMoO4 composite nanorod material on nickel foam prepared in Example 1;

[0045] Fig.12 This is a comparison diagram of the linear scan cyclic voltammetry (LSV) of the NiCoP / CoMoO4 composite nanorod material in situ grown on nickel foam prepared in Example 1 and the initial cobalt molybdate material. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0048] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0049] The nickel foam, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate, sodium hypophosphite, anhydrous ethanol and the like used in the present invention can be directly purchased from sales manufacturers in the market.

[0050] Example 1

[0051] The method for preparing three-dimensional structured NiCoP / CoMoO4 composite nanorods comprises the following steps:

[0052] 1) Preparation of clean nickel foam:

[0053] Cut a piece of nickel foam 2cm×3cm into a 50mL beaker, add 50mL 3M hydrochloric acid solution into the beaker and ultrasonicate for 15min, then pour out the hydrochloric acid, add anhydrous ethanol and ultrasonicate for 15min, then pour out the anhydrous ethanol, finally add deionized water to wash and ultrasonicate for 15min. After the ultrasonication, take out the nickel foam and vacuum dry it at 60℃ for 6h.

[0054] 2) Preparation of cobalt molybdate material loaded on nickel foam:

[0055] Weigh 305 mg of cobalt nitrate hexahydrate and 556 mg of ammonium molybdate tetrahydrate into a 50 mL beaker, add 30 mL of deionized water, and ultrasonicate for 10 minutes to accelerate the dissolution of the reagents, then stir for 5 minutes to disperse the reagents evenly. Pour the prepared solution into a 50 mL polytetrafluoroethylene-lined stainless steel reactor and add a piece of clean nickel foam treated as above. React the reactor in an oven at 150 ° C for 6 hours. After the reaction is completed and cooled to room temperature, take out the nickel foam in the reactor, wash it with deionized water and ethanol 3 times respectively, and vacuum dry it at 60 ° C for 6 hours to obtain the cobalt molybdate material loaded on the nickel foam. The surface of the obtained cobalt molybdate material is smooth and flat, and the material is relatively uniform.

[0056] 3) Preparation of Co(OH)2 / CoMoO4:

[0057] Weigh 1683 mg of potassium hydroxide into a 50 mL beaker and add 30 mL of deionized water. Ultrasonicate for 10 min, then stir for 5 min to obtain a 1 M potassium hydroxide solution, transfer it to a 50 mL polytetrafluoroethylene-lined stainless steel reactor, and add the prepared materials. The reactor was reacted at 120 ° C in an oven for 5 h. After the reaction was completed and cooled to room temperature, the nickel foam in the reactor was taken out and washed with deionized water and ethanol for 3 times, respectively, and vacuum dried at 60 ° C for 6 h to obtain Co(OH)2 / CoMoO4. The surface of the material becomes rough, while the rod shape of the material itself is retained.

[0058] 4) Preparation of NiCo(OH)2 / CoMoO4:

[0059] Weigh 2.035g of nickel nitrate hexahydrate into a 100mL beaker, add 70mL of deionized water, and after ultrasonic stirring, obtain a 0.1M nickel nitrate solution. Immerse the prepared Co(OH)2 / CoMoO4 in the solution and let it stand for 1h. After the reaction is completed, take out the nickel foam, wash it with deionized water and ethanol three times respectively, and vacuum dry it at 60℃ for 6h to obtain NiCo(OH)2 / CoMoO4. The morphology of the material does not change after ion exchange.

[0060] 5) Weigh 0.4g of sodium hypophosphite in a porcelain boat, put it in the upstream of the tube furnace, put the prepared NiCo(OH)2 / CoMoO4 in the downstream porcelain boat, heat it up at a rate of 5℃ / min, and anneal it at 400℃ for 2h in a nitrogen atmosphere. After the reaction is completed, take out the sample to obtain the nanorods of the three-dimensional NiCoP / CoMoO4 composite material. After phosphating, the material still maintains a stable rod-like structure, and the subsequent proof is that the surface cobalt nickel phosphide is a mesoporous structure.

[0061] Characterization of 3D NiCoP / CoMoO4 composites:

[0062] The morphology of the product obtained in Example 1 was analyzed by scanning electron microscopy (SEM). Figure 1 As shown, the prepared sample is a three-dimensional nanorod structure, and the surface of the rod appears to be very rough.

[0063] The morphology of the product obtained in Example 1 was analyzed by transmission electron microscopy (TEM). Figure 2 As shown, it shows that the prepared sample is a three-dimensional nanorod structure, and the surface of the rod is full of pore structures.

[0064] The pore analysis of the product obtained in Example 1 was performed using a specific surface area and porosity analyzer. The results are as follows: Figure 3 As shown, the surface pores of the prepared sample are mesoporous structures with pore sizes distributed in the range of 2-5 nm.

[0065] The product obtained in Example 1 was tested by X-ray diffraction (XRD). Figure 4 The obtained spectrum is completely consistent with the NiCoP diffraction peak corresponding to JCPDS standard card NO.71-2336. This XRD pattern can well prove the successful formation of cobalt nickel phosphide on the surface of cobalt molybdate.

[0066] The product obtained in Example 1 was examined by high resolution transmission electron microscopy (HRTEM). Figure 5 The lattice fringes correspond to the (-1 3 1) crystal plane of CoMoO4 and the (1 1 1) crystal plane of NiCoP, indicating the successful preparation of NiCoP / CoMoO4 composite materials.

[0067] The elemental mapping analysis of the sample obtained in Example 1 was performed using a scanning electron microscope (SEM-Mapping). The results are as follows: Figure 6 As shown. The obtained spectrum proves that Co, Ni, P, Mo, and O elements are evenly distributed in the nanorods. This mapping diagram better proves that the material is a NiCoP / CoMoO4 composite material.

[0068] Example 2

[0069] The method for preparing three-dimensional structured NiCoP / CoMoO4 composite nanorods comprises the following steps:

[0070] 1) Preparation of clean nickel foam: same as in Example 1;

[0071] 2) Preparation of cobalt molybdate material supported on nickel foam: same as in Example 1;

[0072] 3) Preparation of Co(OH)2 / CoMoO4: Same as Example 1;

[0073] 4) Preparation of NiCo(OH)2 / CoMoO4: same as Example 1;

[0074] 5) Weigh 1.0g of sodium hypophosphite in a porcelain boat, put it in the upstream of the tube furnace, put the prepared NiCo(OH)2 / CoMoO4 in the downstream porcelain boat, heat it up at a rate of 5℃ / min, and anneal it at 400℃ for 2h in a nitrogen atmosphere. After the reaction is completed, take out the sample to obtain nanorods of the three-dimensional structure of the NiCoP / CoMoO4 composite material.

[0075] Example 3

[0076] The method for preparing three-dimensional structured NiCoP / CoMoO4 composite nanorods comprises the following steps:

[0077] 1) Preparation of clean nickel foam: same as in Example 1;

[0078] 2) Preparation of cobalt molybdate material supported on nickel foam: same as in Example 1;

[0079] 3) Preparation of Co(OH)2 / CoMoO4: Same as Example 1;

[0080] 4) Preparation of NiCo(OH)2 / CoMoO4: same as Example 1;

[0081] 5) Weigh 0.4 g of sodium hypophosphite in a porcelain boat, put it in the upstream of the tube furnace, put the prepared NiCo(OH)2 / CoMoO4 in the downstream porcelain boat, heat it up at a rate of 5°C / min, and anneal it at 450°C for 2h in a nitrogen atmosphere. After the reaction is completed, take out the sample to obtain nanorods of the three-dimensional structure of the NiCoP / CoMoO4 composite material.

[0082] Example 4

[0083] The method for preparing three-dimensional structured NiCoP / CoMoO4 composite nanorods comprises the following steps:

[0084] 1) Preparation of clean nickel foam: same as in Example 1;

[0085] 2) Preparation of cobalt molybdate material supported on nickel foam: same as in Example 1;

[0086] 3) Preparation of Co(OH)2 / CoMoO4: Same as Example 1;

[0087] 4) Preparation of NiCo(OH)2 / CoMoO4: same as Example 1;

[0088] 5) Weigh 0.4 g of sodium hypophosphite in a porcelain boat, put it in the upstream of the tube furnace, put the prepared NiCo(OH)2 / CoMoO4 in the downstream porcelain boat, heat it up at a rate of 5°C / min, and anneal it at 350°C for 2h in a nitrogen atmosphere. After the reaction is completed, take out the sample to obtain nanorods of the three-dimensional NiCoP / CoMoO4 composite material.

[0089] Application Example 1

[0090] Application of three-dimensional NiCoP / CoMoO4 composite nanorods as electrode materials for hydrogen evolution reaction. Details are as follows:

[0091] The instruments used in the following tests are CHI660E electrochemical workstations, manufactured by Shanghai Chenhua Instrument Co., Ltd.

[0092] The following tests all adopted a three-electrode system, in which the nanorods of the three-dimensional structure of the NiCoP / CoMoO4 composite material prepared in Example 1 were used as the working electrode (1ⅹ1cm); a graphite electrode was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode; and a 1M KOH solution was used as the electrolyte.

[0093] (1) Linear sweep cyclic voltammetry (LSV) test

[0094] At 5mV s -1 The linear scanning cyclic voltammetry curve of the in-situ grown NiCoP / CoMoO4 composite material on nickel foam in Example 1 is as follows: Figure 7 As shown in the figure, the potential range of the curve is 0-0.3V (relative to the standard hydrogen potential). From the LSV graph, it can be seen that when the potential is in the range of 0.1-0.3V, the current density at the corresponding point of the curve increases sharply. -2 At a current density of 1.3 Å, the overpotential of the in-situ grown NiCoP / CoMoO4 nanorod material on nickel foam is only 147 mV. This phenomenon shows that the prepared three-dimensional structure of the NiCoP / CoMoO4 composite nanorods has excellent electrocatalytic hydrogen evolution performance.

[0095] The calculation formula of electric potential is: E RHE / V=E Ag / AgCl +(0.059pH+0.197V); tested under IR compensation.

[0096] (2) Cyclic voltammetry (CV) test of electrochemical double layer capacitors

[0097] The CV graphs were measured at a scan rate of 20 mV s -1 , 40mV s -1 , 60mV s -1, 80mV s -1 The test voltage range is -0.98 to -0.88 V (relative to the silver / silver chloride electrode), which is not a Radius electromagnetic effect, and the cyclic voltammogram of the electrochemical double layer capacitor in Example 1 is obtained, as shown in FIG. Figure 8 shown.

[0098] (3) Electrochemically active surface area (ECSA) test

[0099] The figure is from Figure 8 The calculation formula of electrochemical active surface area is: ECSA / cm 2 =C dl / C s , where C dl is the electrochemical double layer capacitance, which is obtained from the relationship between capacitance current and scan rate; where C s Indicates the specific electrochemical double layer capacitance (0.04mF cm -2 ). After calculation, the electrochemical active surface area diagram in Example 1 is obtained. Fig. 9 It can be seen that the electrochemically active surface area of ​​the NiCoP / CoMoO4 composite material grown in situ on nickel foam is 52.2 mF cm -2 , indicating that the material has a large electrochemically active surface area for hydrogen evolution reaction.

[0100] (4) Electrochemical impedance spectroscopy (EIS) test

[0101] The electrochemical impedance spectroscopy method was used to obtain the AC impedance spectrum of the NiCoP / CoMoO4 composite electrode grown in situ on nickel foam, such as Fig.10 As shown. The intersection of the impedance spectrum and the real axis is the internal resistance of the NiCoP / CoMoO4 composite material grown in situ on nickel foam, including the resistance of the active material itself, the resistance of the electrolyte, and the contact resistance between the active material and the electrolyte. It can be seen that the NiCoP / CoMoO4 composite material grown in situ on nickel foam has a very small charge transfer resistance, which is due to the mesoporous structure constructed on the surface of the material providing abundant reaction sites for the catalytic reaction, which shows that the NiCoP / CoMoO4 composite material grown in situ on nickel foam can be used as an excellent electrocatalyst material for hydrogen evolution.

[0102] (5) Chronopotentiometry (CP) test

[0103] The hydrogen evolution stability diagram of the NiCoP / CoMoO4 composite electrode in situ grown on nickel foam was obtained by chronopotentiometry, as shown in Fig.11 As shown. At 50mA / cm -2At a current density of , the NiCoP / CoMoO4 composite material continuously and stably evolved hydrogen for 100 h, demonstrating the good stability of the NiCoP / CoMoO4 composite material.

[0104] Comparison of the linear scan cyclic voltammetry (LSV) of the in-situ grown NiCoP / CoMoO4 composite nanorod material on nickel foam and the initial cobalt molybdate material prepared in Example 1. Compared with the original cobalt molybdate material, its hydrogen evolution performance and conductivity are greatly improved, thereby achieving efficient electrocatalytic performance.

[0105] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing three-dimensional structured NiCoP / CoMoO4 composite nanorods, characterized in that: The preparation method comprises the following steps: 1) mixing a cobalt source and a molybdenum source in water, adding nickel foam, and performing a hydrothermal reaction to obtain cobalt molybdate; 2) placing the product of step 1) in an alkaline solution and heating the solution to react, thereby obtaining Co(OH)2 / CoMoO4; 3) placing the product of step 2) in a nickel source solution, allowing it to stand and soak, to obtain NiCo(OH)2 / CoMoO4; 4) Phosphating the product of step 3) to obtain three-dimensional structured NiCoP / CoMoO4 composite nanorods.

2. The preparation method according to claim 1, characterized in that: In step 1), the molar ratio of the cobalt source to the molybdenum source is 2-2.5:

1.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the hydrothermal reaction has a reaction temperature of 150° C. and a reaction time of 6 h.

4. The preparation method according to claim 1, characterized in that: In step 2), the alkali solution is a potassium hydroxide solution with a concentration of 1 mol / L; the volume of the alkali solution is the same as the volume of water in step 1).

5. The preparation method according to claim 1 or 4, characterized in that: In step 2), the heating reaction has a reaction temperature of 120° C. and a reaction time of 5 h.

6. The preparation method according to claim 1, characterized in that: In step 3), the molar amount of nickel ions in the nickel source solution is 6-7 times the molar amount of the cobalt source in step 1).

7. The preparation method according to claim 1, characterized in that: In step 4), sodium hypophosphite is used for phosphating; the molar amount of the sodium hypophosphite is 4-12 times the molar amount of the cobalt source in step 1).

8. The preparation method according to claim 1 or 7, characterized in that: In step 4), the phosphating reaction atmosphere is high-purity nitrogen, the temperature is 350-450° C., and the time is 2 hours.

9. A three-dimensional NiCoP / CoMoO4 composite material nanorod prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the three-dimensional structured NiCoP / CoMoO4 composite material nanorods according to claim 9, characterized in that: Application of hydrogen evolution electrocatalysts.

Citation Information

Patent Citations

  • Cobalt phosphate and molybdenum trioxide composite nanorod array three-dimensional electrode material and preparation method and application thereof

    CN113699552A